Registered Reports With Developmental and Secondary Data: Some Brief Observations and Introduction to the Special Issue. Issue 4 (August 2020) - Syed, Moin; Donnellan, M. Brent
Registered reports are a relatively new type of journal article format in which the decision to publish an article is based on sound conceptualization, methods, and planned analyses rather than the specific nature of the results. Registered reports are becoming increasingly instituted in journals across the sciences but mostly in experimental contexts. Relatively few of these journals pertain directly to developmental research with adolescents, emerging adults, and adults, which tend to use more complex methods, or at least methods that involve a greater degree of flexibility. This article describes lessons learned through editing a special issue focused on registered reports based on analyses of a single existing data set, the Emerging Adulthood Measured and Multiple Institutions 2 project. These observations should be helpful for researchers interested in preparing registered report submissions using developmental and secondary data.